Effect of Islamicity Performance Index on Profitability of Sharia Commercial Banks - Afifatuz Zakiyyah; Puspitasari, Novi; Ulfa Hardinawati, Lusiana (Journal of Management Research and Studies, 2023)
Dramatic development of sharia economic has changed the existing structure of banking industry and created the so called sharia banking. Sharia Commercial Banks as the implementer of sharia banking feel necessary to maintain and improve performance and profitability. The objective of this research is to understand and analyze the effect of performance of Sharia Commercial Banks on profitability. Research population includes all Sharia Commercial Banks in the registry of Financial Services Authority in period 2020. Sampling technique is purposive sampling. Research sample with criteria is 6 Sharia Commercial Banks. Panel data regression is used as data analysis method because this research is processing cross-section data and time series data. The results of research show that Profit Sharing Ratio and Islamic Income Ratio have negative effect but not significant on profitability of Sharia Commercial Banks, Zakat Performance Ratio has negative and significant effect on profitability of Sharia Commercial Banks, and Equitable Distribution Ratio has positive and significant effect on profitability of Sharia Commercial Banks.